2011
DOI: 10.1371/journal.pone.0016304
|View full text |Cite
|
Sign up to set email alerts
|

Malectin Participates in a Backup Glycoprotein Quality Control Pathway in the Mammalian ER

Abstract: Malectin is a conserved, endoplasmic reticulum (ER)-resident lectin that recognizes high mannose oligosaccharides displaying terminal glucose residues. Here we show that Malectin is an ER stress-induced protein that selectively associates with glycopolypeptides without affecting their entry and their retention in the Calnexin chaperone system. Analysis of the obligate Calnexin client influenza virus hemagglutinin (HA) revealed that Calnexin and Malectin associated with different timing to different HA conforme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
68
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(71 citation statements)
references
References 42 publications
3
68
0
Order By: Relevance
“…Malectin was found to associate with endogenous aquaporin-2 in a large-scale proteomics study (Barile et al 2005). However, recent studies suggest that malectin binds aberrant substrates in the ER (Chen et al 2011;Galli et al 2011). This raises the question if malectin acts early in the maturation process, how can it already distinguish between native and aberrant proteins?…”
Section: Carbohydrate-binding Chaperonesmentioning
confidence: 99%
“…Malectin was found to associate with endogenous aquaporin-2 in a large-scale proteomics study (Barile et al 2005). However, recent studies suggest that malectin binds aberrant substrates in the ER (Chen et al 2011;Galli et al 2011). This raises the question if malectin acts early in the maturation process, how can it already distinguish between native and aberrant proteins?…”
Section: Carbohydrate-binding Chaperonesmentioning
confidence: 99%
“…Because malectin, a novel ER-resident protein, was first reported by the Xenopus laevis proteomic study, its selective binding to di-glucosylated high mannose-type N-glycans has led to much speculation regarding its function (12,13). By analogy with the mono-glucosylated N-glycan-binding lectins, CNX and CRT, which play an essential role in the folding of glycoproteins, malectin is also suggested to be involved in the quality control of glycoproteins in the ER.…”
Section: Discussionmentioning
confidence: 99%
“…By analogy with the mono-glucosylated N-glycan-binding lectins, CNX and CRT, which play an essential role in the folding of glycoproteins, malectin is also suggested to be involved in the quality control of glycoproteins in the ER. In fact, Galli et al (13) recently showed that malectin associates with newly synthesized glycoproteins, especially those with misfolded conformations, and subsequently interferes with their secretion. These results were confirmed by this study, which showed that malectin preferentially co-precipitated with misfolded AT NHK but not with wild-type AT (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Briefly, newly synthesized N-linked glycoproteins are glycosylated with 14 sugars donated from a dolichol-linked lipid via oligosaccharyl transferase (Das and Heath 1980). Following the sequential removal of the terminal glucose by glucosidase I (Hettkamp et al 1984;Bause et al 1989), the glycoprotein may then be recognized by the protein malectin (Schallus et al 2008;Chen et al 2011;Galli et al 2011), potentially for presentation to glucosidase II for removal of the second glucose residue (Burns and Touster 1982;Reitman et al 1982;Pelletier et al 2000). The resulting mono-glucosylated glycoprotein is then a client for association with calnexin or calreticulin (Hammond et al 1994;Zapun et al 1997;Schrag et al 2003).…”
Section: The Calnexin Cycle As Extended Er Microdomainsmentioning
confidence: 99%